Broken Ribs, Split Skulls: Reconstructing Trauma Patterns in the Monastic Burials at the Holy Trinity Church (Vilnius) - Kozakaitė, Justina; Jakulis, Martynas (Lietuvos istorijos studijos, 2017)
While bioarchaeological monastery researches draw substantial differences between the secular and monastic lifestyles, the former injury rate indicates no shocking results. A relatively small number of fractures demonstrated that monks were not predisposed to injuries due to their specific lifestyle and daily activities. In 2015 and 2016, an archaeological investigation at The Holy Trinity church and its crypt revealed 17th–18th century burials belonging to the Basilian monks. These findings provided a unique opportunity to study the monastic lifestyle in the Grand Duchy of Lithuania based on the tendencies of trauma. Common rib fractures, violent injuries and high-energy trauma painted a vivid and unusual life picture of the 17th–18th century Basilian monastery of Vilnius.